The life and activities of Jonas Matulionis - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 2023)
A brief biography of the mathematician prof. J. Matulionis is presented. The accent is made on the most significant links of his life – the study period and the longevous work at the Kaunas University of Technology.The textbook  `  `  Higher  mathematics'', prepared by J. Matulionis, is analysed. The textbook appears to be the very first (after the war) means on mathematics in Lithuanian, for higher technical schools.
Keywords: history of mathematics; Lithuanian mathematics textbooks